Use of evidence in health professions education: Attitudes, practices, barriers and supports. (2nd September 2019) - Thomas, Aliki; D. Gruppen, Larry; van der Vleuten, Cees; Chilingaryan, Gevorg; Amari, Fatima; Steinert, Yvonne
Abstract: Introduction: Health professions educators are increasingly called upon to apply an evidence-informed approach to teaching and assessment practices. There is scant empirical research exploring educators' attitudes, practices, and perceived barriers and supports to using research evidence in educational practice. Methods: We conducted a survey of AMEE members to explore three domains related to evidence-informed health professions education: (1) attitudes; (2) practices; and (3) supports and barriers. Analyses involved descriptive statistics to characterize participants' responses per domain. Chi-Square statistics were carried out to examine differences among the demographic variables on a subset of items in each of the three survey sections. Results: Three hundred ninety-six (∼10%) participants representing health professions educators (HPEs) and non HPEs (e.g. PhDs) and different roles (e.g. teacher, administrator) completed the survey. Attitudes toward evidence-informed HPE were generally favorable. Several barriers preclude participants from engaging in evidence-informed approaches to health professions education (HPE). Discussion: This study provides preliminary evidence on the attitudes toward and perceived barriers and supports of research use in HPE from different groups of HP educators, clinicians, and administrators. The findings for each of the three domains require additional exploration using qualitative methodologies. Conclusion: Targeted interventions designed to increase the uptake of research in HPE should consider different stakeholder groups' perceptions regarding these approaches, current vs. best practices, and factors that may impede evidence-informed approaches.